Difference between RP2 and RP3 phenotypes in X linked retinitis pigmentosa. Issue 10 (1st October 1999) - Flaxel, Christina J; Jay, Marcelle; Thiselton, Dawn L; Nayudu, Mani; Hardcastle, Alison J; Wright, Alan; Bird, Alan C
Abstract : AIM: X linked retinitis pigmentosa (XLRP) has two genetic loci known as "RP2" and "RP3". Clinical features reported to differentiate RP2 from RP3 include a higher prevalence of myopia and primary cone dysfunction in RP2, and late onset night blindness and tapetal reflex in RP3. Members from 14 XLRP families were examined in an attempt to verify these differences. METHODS: 16 affected males and 37 females from 14 XLRP families assigned as either RP2 or RP3 by haplotype analysis and/or by heterogeneity analysis were examined. Members of all 14 families who were willing to participate but unavailable for examination were contacted and detailed interviews carried out. RESULTS: No clear phenotypic differences were found that could be used to reliably differentiate RP2 from RP3 with respect to myopia and onset of night blindness. The tapetal reflex was also found to be present in carriers of both RP2 and RP3. CONCLUSIONS: XLRP is a heterogeneous class of rod degenerative disorders with no clear phenotypic differentiation between the two genetic loci RP2 and RP3. There is a continuum of clinical presentations which can be seen in both RP2 and RP3, but the features within a given family tend to be consistent. However, interfamilial variability is prevalent leading to a wide range of clinical presentations and more than one abnormal allele at each gene locus cannot be excluded.